Locational conditions, cooperation, and innovativeness: evidence from research and company spin-offs - Anna Lejpras; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper has two goals. First, it analyzes the extent to which the innovativeness of spin-offs, either born from a research facility or from another company, is influenced by locational conditions. Second, it provides evidence on how important local cooperation links are in comparison to nonlocal ones. Using a sample of approximately 1,500 East German firms from knowledge-intensive sectors, we estimate a structural equation model applying the partial least squares method. We find that proximity to local research institutes and universities is the most influential factor for the cooperation intensity of spin-offs. Furthermore, the higher the cooperation intensity, the greater the innovativeness of a firm. Moreover, the results indicate that it is not the local but the nonlocal cooperation ties that are more conducive to innovativeness of research spin-offs. The findings also highlight that the innovativeness of research spin-offs with solely local links is strongly depends on support from various authorities and institutions.
Keywords: M13; O18; R3; 330; Research and Company Spin-Offs; Locational Conditions; Cooperation Intensity; Innovativeness; Structural Equation Modeling; Partial Least Squares Approach; Innovation; Betriebsaufspaltung; Standortfaktor; Forschungskooperation; Region; Industrielle Forschung; Business Network; Neue Bundesländer